QUEUING SYSTEM WITH BULK SERVICE AS A MODEL OF SCTP PROTOCOL FUNCTIONING - Litvinov, A.; Bredikhin, V. (Municipal economy of cities. Series: «Economy science», 2024)
The article presents the results of developing a model for the Stream Control Transmission Protocol functioning as a queuing system with bulk service. It constructs a graph of states and transitions for deriving linear and differential equation systems regarding the state probabilities. We obtain explicit solutions to analyse the basic SCTP functioning.